Hubungan Brand Equity (Brand Awarenees, Brand Associations, Perceived Quality) dengan Keputusan Pemanfaatan Klinik Laktasi di Rumah Sakit Muhammadiyah Lamongan - Fajar Ni’Syinta Armadani; Supriyadi Supriyadi; Nurnaningsih Herya Ulfah (Preventia : The Indonesian Journal of Public Health, 2018)
Abstrack: The visit number of patient at the lactation clinic of Muhammadiyah Lamongan Hospital tends to be small and decreases every year. A decrease in the visit number of patient may indicate that the utilization of health services is lacking. In utilizing health services, consumers are influenced by several considerations. One of affects consumer considerations is brand equity (brand awareness, brand associations, and perceived quality). This study aims to determine the relationship of brand equity (brand awareness, brand associations, and perceived quality) with the decision of lactation clinic utilization at Muhammadiyah Lamongan Hospital. This research used correlational quantitative design to know the relationship between brand awareness (X1), Brand Associations (X2), perceived quality (X3), with decision of utilization of lactation clinic at Muhammadiyah Lamongan Hospital (Y). The population in this research was all patient who used lactation clinic at Muhammadiyah Lamongan Hospital and the sample were 32 patients, who visited the lactation clinic at Muhammadiyah Lamongan Hospital during April until May 2017. Technique of collecting data used questionnaire. Data analysis was correlation test, multiple linear regression test. Based on the results of the analysis, this study shows that there is a significant relationship simultaneously between brand awareness, brand associations, and perceived quality with the decision of utilization of lactation clinic at Muhammadiya Lamongan Hospital. Based on the result of coefficient of determination (R2) of 0.569 which means that Brand Awareness (X1), Brand Associations (X2), Perceived Quality (X3) have contribution equal to 56.9% to decision of utilization to laktasi clinic at Muhammadiyah Hospital Lamongan (Y).Keywords:Brand Awareness, Brand Associations, Perceived Quality, Utilization of Health Care Service.Abstrak: Jumlah kunjungan pasien di klinik laktasi Rumah Sakit Muhammadiyah Lamongan cenderung sedikit dan mengalami penurunan setiap tahun. Penurunan jumlah kunjungan pasien dapat menunjukkan bahwa pemanfaatan pelayanan kesehatan yang kurang.Dalam memanfaatkan pelayanan kesehatan,konsumen dipengaruhi oleh beberapa pertimbangan, salah satu yang mempengaruhi pertimbangan konsumen ialah Brand Equity.Penelitian ini dilaksanakan dengan tujuan untuk mencari hubungan antara Brand Awareness, Brand Associations, dan Perceived Quality dengan keputusan pemanfaatan klinik laktasi di Rumah Sakit Muhammadiyah Lamongan. Rancangan penelitian ini adalah kuantitatif korelasional dengan sampel sebanyak 32 orang. Teknik pengumpulan data menggunakan kuesioner. Analisis data menggunakan uji korelasi pearson dan uji regresi linier berganda. Hasil analisis penelitian didapatkan ada hubungan yang signifikan antara Brand awareness, Brand asssociations, Perceived quality secara bersama-sama dengan keputusan pemanfaatan klinik laktasi di Rumah Sakit Muhammadiyah. Berdasarkan hasil koefisien determinasi (R2) sebesar 0,569 yang berarti bahwa Brand Awareness (X1), Brand Associations (X2), Perceived Quality (X3) mempunyai kontribusi sebesar 56,9% terhadap keputusan pemanfaatan terhadap klinik laktasi di Rumah Sakit Muhammadiyah Lamongan (Y). Kata kunci: Brand Awareness, Brand Associations, Perceived Quality, Keputusan Pemanfaatan Pelayanan Kesehatan